ChemInform Abstract: Functionalized BINOL‐mono‐PHOS for Multinuclear Cu‐Catalysts in Asymmetric Conjugate Addition of Organozinc Reagents. Issue 46 (18th November 2014) - Endo, Kohei; Yakeishi, Sayuri; Hamada, Daisuke; Shibata, Takanori
Abstract The syntheses of ligands (I) as well as derivatives thereof are described.